If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x-9=11x-90+27
We move all terms to the left:
11x-9-(11x-90+27)=0
We add all the numbers together, and all the variables
11x-(11x-63)-9=0
We get rid of parentheses
11x-11x+63-9=0
We add all the numbers together, and all the variables
54!=0
There is no solution for this equation
| 11-3x=–31 | | 21,5÷x=3,5 | | 8x2-43x-30=0 | | 9x-3(x-5)=2(x+10) | | 6x^2-2x-116=0 | | 3x+9=100-10x | | 144π=πr^2*9 | | 2x-4=0;X=1,2,-2 | | 2x+12=-2x-10 | | x^2+12x=1728 | | 2x+4=4x-44 | | 2/5x+4/5x=-4/15x+44/5 | | x-1=3·x-3 | | 3/4c=4650 | | 3/4=4650d | | 5(2x-5)+8x=4(5x-7) | | 3/4p=4650 | | 3(x-2)=-2(3-2x | | -5x+5=9-3x+2 | | 7-8=3x+20 | | 4c−5=1 | | x−3/2=11 | | 3*10x=0,03 | | 38000=3,8*10x | | 7,5•x=60 | | 2x-15,7=03 | | (5t-2)^2=36 | | 4x-2x+-3x=-3+8+7 | | 9=0.6+n | | -2-a=10 | | -2-2x=3x-12 | | 7x÷9=-14 |